AN ANALYSIS OF TEACHING AND LEARNING ENGLISH SECOND LANGUAGE (CASE STUDY ON NONFORMAL EDUCATION INSTITUTION) - SOLEHAH, MARATU; HERYATUN, YAYU; ANITA, ANITA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to analyze the English language learning process at nonformal education namely Kumon Citraland Puri Serang. The objectives of this research are 1) to examine how the strategy used by Kumon citraland on teaching English. 2) to investigate what is the media used by Kumon Citraland Puri Serang to teach English. 3) to analyze the material used by Kumon Citraland Puri Serang on teaching English. 4) to analyze how to evaluate students. This study is descriptive qualitative research that used interviews, observation and documentation to collect data. Based on the research results, it shows that Kumon Citraland Puri Serang has its own learning strategy which is different from other courses, where Kumon Citraland uses a placement test to determine the starting point/basic level that will be taught according to the student's abilities. Kumon Citraland Serang also uses several learning media including audio and CD players, text books, practice sheets, the My Kumon application, and Kumon Konek. The material taught at Kumon is very diverse, starting from the lowest level, namely level 7A, to the highest level, namely level O. Each student will move up a level when they have completed the material at one level, namely 200 practice sheets. As evaluation material, Kumon Citralan Puri also provides several summary questions from each level to find out how far students understand the material that has been taught. These questions consist of listening, writing, reading comprehension and speaking skills.